Soil Resource Inventory Of The Main Campus Kerala Agricultural University Vellanikkara: Part 1 (east) - Seena E (Department Of Soil Science And Agricultural Chemistry,College Of Horticulture, 2000)
The present study was conducted in the main campus of Kerala Agricultural University, Vellanikkara with the objective of preparation of a detailed soil resource inventory. The total area of the campus is 384.56 ha. The inventory under this report was carried out covering the eastern part of the campus comprising an area of 214 ha which is divided into 25 blocks. The study mainly concentrated on the resource potential of the campus with respect to soil resource. Here an attempt has been made to evaluate the physical, chemical and electrochemical properties of the soil. One hundred and ninety eight samples each from surface(O - 20 cm) and sub surface(20 -40 cm) layers collected at a grid size of 80 m2 were analysed for the above properties. Soil samples collected from different parts of the campus were predominantly gravelly in nature both in the case of surface and subsurface samples. In the textural analysis majority of the phases were coming under clay loam. Irrespective of depth, in majority of the phases, surface and subsurface samples were coming under same textural classes. In general almost all the soils were acidic in nature. This shall be due to the high rainfall and subsequent leaching. Electrical conductivity of the soil samples was found to be very low both in the case of surface and subsurface soils. Buffer pH was estimated to find out the lime requirement of the soils. It was found that buffer pH varied widely among the samples and so also the lime requirement. An increase in organic carbon content with depth was observed in a few phases. Almost 91 % of the surface and 90% of the sub surface samples analysed were medium in fertility, 7 per cent each of the surface and sub surface samples were coming under high fertility class and the remaining 2 and 3 per cent were low in organic carbon status. Available phosphorus content recorded low values in almost all the samples both in the case of surface and subsurface soils. 78% of surface and 84 %of sub surface samples were rated as low in fertility while 17 and 13 % were medium in fertility and only 5 and3 per cent of the samples from surface and sub surface were high in fertility. The results